Principles of Acceptance and Mistakes in the Implementation of Criminal Procedural Decisions - ABZALBEKOVA, Maral T.; ZHAMIYEVA, Roza M.; ZHAKUPOV, Bakytzhan A. (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
The relevance of the study problem is caused by the need to ensure the legality, validity and substantiation of criminal procedural decisions, which ultimately leads to the achievement of goals and objectives of criminal proceedings. Purpose of the article : the purpose of the article is to develop the principles of decision-making by the subject of criminal procedural activity, as well as identifying the typical mistakes in their implementation. Study methods : The basis of problem solving in terms of criminal procedural decision-making and implementation is the system-based and activity approach and the methodological provisions of the decision-making theory, which allowed to identify patterns in the process of criminal procedural decision-making and implementation by the representative of criminal proceeding bodies and other participants of the proceeding. Study results : The principle systems of decision-making by the subject of criminal procedural activity is provided; the levels and stages of procedural decision-making and implementation are outlined, typical mistakes made by the subject of criminal procedural decision are determined taking into account the level of decision-making and the violated principle. Practical relevance : The identified patterns, principles, stages and levels of decision-making, as well as the typical mistakes formulated, will have a significant impact on improving the viability of decisions made in the criminal proceedings, and recommendations based on them contribute to ensuring the rule of law in the activities of judges, investigators, prosecutors and other participants in the proceedings.